Clean Water Payment Management Information System Using Extreme Programming Method - Amrullah Fadhil; Suendri (Jurnal Informasi dan Teknologi, 2024)
In the dynamic information age, society has transitioned into an informational society where information technology plays an important role in this transformation. Information systems, as a support for the managerial functions of organizations, are developing with the integration of technology to increase effectiveness and efficiency. The growth and increase of the population in an area increases the need for basic services, including the provision of clean water. Efficient management, especially in the aspect of the payment system, is crucial to ensure the availability of clean water as a human right. In this context, the development of a clean water payment management information system using the Extreme Programming method is very helpful for researchers in developing the system quickly and responsively. This system is expected to simplify the payment process by focusing on efficiency, accuracy, transparency, and accessibility for users. This study aims to design and implement a clean water payment management information system adopting the Extreme Programming method, with the aim of improving clean water payment services as a whole. An evaluation of the system will be carried out to ensure suitability with the needs of users and their ability to overcome the problems faced in the management of clean water payments. Thus, the results of this study are expected to make a significant contribution to the understanding and development of an effective and sustainable management information system for clean water payment services.